Sutureless Valve Implantation via Mini J-Sternotomy: A Single Center Experience with 2 Years Mean Follow-up - Fischlein, Theodor; Pfeiffer, Steffen; Pollari, Francesco; Sirch, Joachim; Vogt, Ferdinand; Santarpino, Giuseppe (The Thoracic and Cardiovascular Surgeon, 2015)
Introduction Despite increased operative time, minimally invasive cardiac surgery is associated with a lower morbidity than conventional aortic valve replacement (AVR). On the other hand, sutureless aortic bioprostheses have the potential of simplifying implantation, as it reduces the ischemic time. Our aim was to investigate the outcome of a sutureless AVR through a mini-sternotomy.Materials and Methods Since March 2010, a total of 262 patients affected by aortic valve stenosis underwent AVR with a sutureless bioprosthesis (Perceval, Sorin Group, Saluggia, Italy). Of these, 145 patients (mean age 77.8 ± 4.7 years, 80 women) underwent surgical AVR through a mini J-sternotomy. Clinical and echocardiographic data were evaluated.Results Patients received a size: S(12), M(49), L(67), or XL(17) prostheses, either as isolated (131) or combined procedures (14) including 2 redo patients who had undergone coronary artery bypass grafting via full sternotomy previously. Mean logistic EuroSCORE (I) was 9.9 ± 5.9%, and mean aortic cross-clamp time was 38 ± 12 minutes (35 ± 11 minutes in isolated procedures). Two conversions to full sternotomy were necessary because of bleeding. Thirty-day mortality was 2.1% (all noncardiac deaths); mean hospital stay was 11.6 ± 4.9 days. We recorded 11 pacemaker implantations (7.6%). At follow-up (23.5 ± 14.4 months), five patients were dead (three noncardiac and two cardiac deaths). At echocardiographic control, mean transprosthetic gradients were as follows: 12.8 ± 4.9, 12.5 ± 4.5, 11.8 ± 4.7 mm Hg, postoperatively at 6 months, 1 year, and 2 years, respectively. No paravalvular leaks were recorded.Conclusion The sutureless bioprosthesis shows satisfactory clinical and hemodynamic results. Owing to its simple implantation technique, it represents a good support for minimally invasive access surgery via J-sternotomy.
Keywords: aortic valve; outcomes; minimally invasive surgery; cardiac